2014
DOI: 10.3892/br.2014.245
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of regucalcin in heart calcium signaling: Insight into cardiac failure (Review)

Abstract: Regucalcin was first identified in 1978 as a regulatory protein of Ca2+ signaling in liver cells. Regucalcin was shown to play a multifunctional role in cell regulation, such as maintainance of intracellular Ca2+ homeostasis and suppression of signal transduction, protein synthesis, nuclear function, cell proliferation and apoptosis in various types of cells and tissues. Cardiac excitation-contraction coupling is based on the regulation of intracellular Ca2+ concentration by the Ca2+ pump in the sarcoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In addition, Matsumoto et al showed that cytosolic calcium regulates autophagy-related gene expression in autophagy-deficient mice [18] and that cytosolic Ca 2+ signaling is a critical regulator of cardiac myocyte function [13]. A pivotal anti-senescence marker, SMP30 (senescence marker protein 30), has been reported to regulate intracellular Ca 2+ homeostasis [19,20,21] and play a pathophysiological role in the tight regulation of Ca 2+ -related cell functions [22]. Recently, intracellular Ca 2+ signaling has been reported to have an important role in the regulation of autophagy [23]; however, its exact function remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Matsumoto et al showed that cytosolic calcium regulates autophagy-related gene expression in autophagy-deficient mice [18] and that cytosolic Ca 2+ signaling is a critical regulator of cardiac myocyte function [13]. A pivotal anti-senescence marker, SMP30 (senescence marker protein 30), has been reported to regulate intracellular Ca 2+ homeostasis [19,20,21] and play a pathophysiological role in the tight regulation of Ca 2+ -related cell functions [22]. Recently, intracellular Ca 2+ signaling has been reported to have an important role in the regulation of autophagy [23]; however, its exact function remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…CaP nanoparticles showed better endogenous VEGF mRNA silencing in cultured pancreatic cancer cells and did not induce significant toxicity at concentrations of up to 25-fold higher concentrations than RNAi-induced concentrations. A high dose of unbound calcium ions can apparently affect the heart because cardiac excitation-contraction is based on regulation of intracellular calcium ion concentration in heart muscle cells[189]. Thus, for systemic delivery of therapeutic siRNA, the CaP nanoparticle was further purified by an ultrafiltration method and approximately 80% of theA C C E P T E D M A N U S C R I P Toriginal calcium contents were removed[171].…”
mentioning
confidence: 99%
“…During Ca2 + -pumping activity in the plasma membrane of HepG2 and LLCPK1 cells, SMP-30 regulates Ca2 + kinetics through modulating the activity Ca2 + -binding proteins, showing that SMP30 can rescue cells from apoptotic death induced by the high intracellular Ca2 + level [ 32 ]. Previous studies have suggested that SMP30 can directly bind to Ca2 + pump, stimulate its activity, and play a multifunctional role in cell regulation, such as intracellular Ca2 + homeostasis maintenance, signal transduction suppression, protein synthesis, nuclear function, cell proliferation, and apoptosis in various types of cells and tissues [ 33 , 34 ]. As an important intracellular Ca2 + regulator, the changes in SMP-30 can be functionally critical to Ca2 + homeostasis during aging.…”
Section: Discussionmentioning
confidence: 99%